THE USE OF COGNITIVE LOAD THEORY IN THE TEACHING OF PROGRAMMING IN COMPUTER SCIENCE IN SECONDARY SCHOOLS - Fayzulloyevich, Kasimov Feruz (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
In the information age, the urgent tasks of processing, storing and using information have become a key part of life. It is also the main task of every educational institution and teacher to train personnel who can perform these tasks at a high level, to ensure the success of young people in the field of information technology.